2020
DOI: 10.1590/1678-4324-2020200059
|View full text |Cite
|
Sign up to set email alerts
|

Mild-intensity Exercise Triggers VEGF in the Digestive Tract Via Both Hypoxic and Nonhypoxic Mechanisms

Abstract: Hypoxia occurs in the splanchnic region during exercise associated with sympathetic activity. In the elderly, vascular insufficiency and low vascular endothelial growth factor (VEGF) expression are observed. Compared to young people, sympathetic signals of older individuals are blunted and more resistant to splanchnic blood flow alterations during exercise. VEGF induces vasodilation responses and hence may retain blood in the splanchnic vascular bed. We hypothesized that regular mild-intensity exercise trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Also, hypoxia-inducible factor-1 alpha (HIF-1α) and reactive oxygen species (ROS) have been shown to activate VEGF. HIF-1α regulates VEGF gene expression and provides the adaptive responses required for gastrointestinal homeostasis maintenance under hypoxia (28). It has been observed that the source of VEGF in the ileocecal region is especially the crypt regions of the surface epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Also, hypoxia-inducible factor-1 alpha (HIF-1α) and reactive oxygen species (ROS) have been shown to activate VEGF. HIF-1α regulates VEGF gene expression and provides the adaptive responses required for gastrointestinal homeostasis maintenance under hypoxia (28). It has been observed that the source of VEGF in the ileocecal region is especially the crypt regions of the surface epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a signaling protein that promotes the growth of new blood vessels. In older adults, gentle exercise may trigger weak VEGF expression through both hypoxic and nonhypoxic mechanisms [82]. Another neurotrophic factor involved in exercise-facilitated neuroprotection is IGF-1.…”
Section: The Effects Of Exercise On Central and Peripheral Factorsmentioning
confidence: 99%
“…Any type of exercise is beneficial to health [7][8][9][10][11][12][13], but given the need to evaluate physical performance and the effects of exercise on diseases, it was necessary to develop models of aerobic [14,15] and sprint exercise training [16]. A voluntary physical exercise (VPE) model for zebrafish has not yet been described, although such model is already widespread in rodents [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%